Foreign body pulmonary vessel embolism and granulomatosis in intravenous drug abuse: An autopsy study - Manveen Kaur; RPS Punia; Rasheeda Mohamedali; Debajyoti Chatterjee; Ranjeev Bhagat; Phiza Aggarwal; Uma Handa; Amandeep Singh (Indian Journal of Pathology and Microbiology)
The abuse of illicit drugs causes a myriad of systemic complications. Intravenous (IV) injection of such drugs poses various additional threats, primarily due to the use of excipient materials in them. Pulmonary artery embolism with foreign material and granulomatosis may be encountered in the lungs on histopathological examination in such cases. In this study, we aimed to analyze the histopathological findings in lungs in postmortem specimens with suspected IV drug abuse. This was a retrospective study of 5 years in which 15 cases of known or suspected history of drug abuse were assessed. The clinical details were compiled, and the hematoxylin and eosin (H and E)-stained microscopic slides were retrieved from the archives for reviewing the histopathological features in lungs submitted for postmortem analysis. All the cases were male, aged 21 to 36 years (median: 27 years). Gross examination revealed edematous lungs in four cases (26.6%). On microscopic examination of the lungs, all the cases (100%) showed the presence of basophilic irregular structures to rod-like pale crystalline refractile material, which was accompanied by a granulomatous reaction in the lumen of the pulmonary arteries. Four of these cases (26.6%) showed birefringence on polarizing microscopy. The use of illicit drugs is becoming widespread, especially among young individuals. IV drug abuse increases the rate of morbidity and mortality by affecting primarily the pulmonary vasculature, particularly pulmonary arteries. An acquaintance with the various patterns of pulmonary involvement in IV drug abuse is essential to arrive at an accurate pathological diagnosis and provide a possible cause of death in such cases.